Impacto del riesgo político en la inversión privada en el Perú, periodo 1992-2018 - Sánchez Dávila, Elmer (2020)
This paper aims to determine the impact of political risk on private investment in Peru. Therefore, the methodology used to achieve this goal is an econometric estimation through an autoregressive distributed lag model (ARDL) from the second quarter of 1992 to the second quarter of 2018 (1992q2 – 2018q2). The paper takes into consideration i) the short- and long-run effects of political risk and ii) whether this risk could be influenced by political regimes. The results show that political risk does not have a significant impact on private investment, neither in the short nor in the long run. In the long run, private investment significatively depends on real GDP, real exchange rate, and the price of copper, while in the short run real GDP is the most important variable. Moreover, the results show that political regime, be that democratic or not, does not have an impact on the evolution of private investment.